Screening at the Dental Office: An Opportunity for Bridging the Gap in the Early Diagnosis of Hypertension and Diabetes in Ghana - Blankson, Paa-Kwesi (Ann Afr Med, 2020)
BACKGROUND: The prevalence of hypertension and diabetes is increasing in Ghana and sub-Saharan Africa. Screening is a useful tool in improving the early detection of both diseases to reduce the mortality and morbidity associated with the conditions. This study set out to determine the prevalence of patients with hypertension and hyperglycemia attending a dental clinic in Accra. METHODS: A cross-sectional study, modeling a screening exercise, was conducted in a major dental clinic in Accra. Hypertension and diabetes were screened for with serial blood pressure checks at rest and random blood glucose measurements, respectively. Other variables were the pulse rate, the respiratory rate, and the background characteristics of respondents. Data were analyzed with Stata Version 14, and descriptive statistics were generated and reported. RESULTS: There were a total of 175 participants in the study, comprising 76 males (43.4%) and 99 females (56.6%). This represented a male-to-female ratio of 0.8:1. The ages ranged from 18 to 86 years, with the median and mean ages of 40 years and 43.1 years (±16.9), respectively. This study found the prevalence of hypertension and hyperglycemia in the dental clinic to be 31.4% and 24.6%, respectively. CONCLUSION: The results of this study demonstrate the importance of the dental clinic in detecting both undiagnosed hypertension and diabetes, as well as those who have previously been diagnosed, but do not have their blood pressure and blood sugar under adequate control. With efficient referrals and follow-up systems in place at dental offices, they could be harnessed as a fertile place for hypertension and diabetes screening.